Evaluation of Protein Choice Feeding Programs When Diets Have Constant Energy Level - Cerrate, S.; Wang, Z.; Coto, C.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2007)
Male broilers of a commercial strain were grown to 10 d of age on a common starter diet and then from 11 to 49 days were offered single diets (control), a choice of starter and finisher diets, isoenergetic choices between 12 and 24 or 32% Crude Protein (CP) diets and isoenergetic choices between 15 and 24 or 32% CP diets. Birds fed the isoenergetic diets varying in protein content had almost similar body weight, feed intake, energy intake and carcass characteristics as did birds fed the control diets or the choice of starter and finisher diets. In general the feed and energy conversions by birds given the choice between 12 and 24 or 32% CP diets were worse than those of birds given the other feed systems; however, the protein consumption and conversion by birds fed the former diets were lower than those of birds fed the latter diets. There was a marked preference for the low protein diets (12 and 15% CP) over the high protein diets (24 and 32% CP), but this preference was reduced when the low protein diets were offered with the 24% CP diet. The levels of protein selected of the isoenergetic diets varying in protein content were lower than those of control diets or choice between finisher and starter diets and declined with age except for the last week of the experiment, possibly due to feed form variation. Birds given the choice between 15 and 24 or 32% CP diets had similar performance, except for slightly better protein conversion but slightly worse energy conversion, as those fed control diets or given a choice of starter and finisher diets; even though these choice-fed broilers chose lower protein contents than did birds fed the other two systems. These data indicate that choice of isoenergetic diets varying in protein content can be used to determine protein requirements of broilers, being more effective and efficient with a narrow range of two protein contents.